2019
DOI: 10.1177/0885066619892218
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inotropes on the Mortality in Patients With Septic Shock

Abstract: Background: Although surviving sepsis campaign guidelines recommend the use of inotropes in the presence of myocardial dysfunction, the effects of inotropes, including epinephrine, dobutamine, and milrinone, on in-hospital mortality in patients with septic shock remains unclear. Materials and Methods: We conducted an international,2-center, retrospective cohort study. The Cox proportional hazards regression model with time-varying covariates was used to investigate whether epinephrine, milrinone, or dobutamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 45 publications
(45 reference statements)
0
29
0
2
Order By: Relevance
“…Therefore, a vicious cycle is established in viral sepsis leading to high mortality despite the current therapies. Epinephrine and dobutamine use in sepsis is reported to be associated with increased mortality and atrial fibrillation [3].…”
mentioning
confidence: 99%
“…Therefore, a vicious cycle is established in viral sepsis leading to high mortality despite the current therapies. Epinephrine and dobutamine use in sepsis is reported to be associated with increased mortality and atrial fibrillation [3].…”
mentioning
confidence: 99%
“…154 Interestingly, Sato et al reported milrinone was not associated with increased mortality in septic shock (HR: 0.885; 95% CI: 0.44-1.79; P = .734), unlike epinephrine and dobutamine. 131 However, milrinone was associated with increased incidence of AF similar to both epinephrine and dobutamine. 131 Milrinone showed no detrimental effects and possibly enhanced cardiac function when used in combination with β-blockers (BBs) in sepsis to combat concerns for catecholamine-induced myocardial depression by avoiding dobutamine.…”
Section: Methodsmentioning
confidence: 98%
“…131 However, milrinone was associated with increased incidence of AF similar to both epinephrine and dobutamine. 131 Milrinone showed no detrimental effects and possibly enhanced cardiac function when used in combination with β-blockers (BBs) in sepsis to combat concerns for catecholamine-induced myocardial depression by avoiding dobutamine. 155,156 Unlike dobutamine, phosphodiesterase inhibitor efficacy is not altered by concomitant BBs, 157 but the specific application of milrinone use preferentially to dobutamine in patients on chronic BB therapy is not established.…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations